2002
DOI: 10.1097/00024720-200208000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Dural Ectasia and Back Pain: Review of the Literature and Case Report

Abstract: Dural ectasia is defined as a ballooning of the dural sac which is more common in patients with connective tissue disorders such as the Marfan syndrome. Several studies have shown that dural ectasia may be associated with such conditions as back pain, headaches, radiculopathies, or incontinence. We present a case of a 52 year old woman with Marfan syndrome who presented with a significantly large anterior sacral meningocele without having associated symptoms. In light of this case, we recommend that asymptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 28 publications
0
21
1
Order By: Relevance
“…It is hypothesized that dural ectasia may cause symptoms through a variety of mechanisms. Possibilities include direct pressure on the periosteum, erosion of bony elements of the lumbosacral spine [Duncan and Esses, 1995;Stern, 1998;Ho et al, 2002], distortion or traction of neural roots [Smith, 1993;Nallamshetty et al, 2002], structural thinning and weakening of the sacrum leading to micro-fractures or instability, direct pressure on abdominal organs by anterior meningocele, shifts in cerebrospinal fluid volume, or increased pressure within focal cysts [Raftopoulos et al, 1993;Sonier et al, 1993;Ahn et al, 2000] (see Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is hypothesized that dural ectasia may cause symptoms through a variety of mechanisms. Possibilities include direct pressure on the periosteum, erosion of bony elements of the lumbosacral spine [Duncan and Esses, 1995;Stern, 1998;Ho et al, 2002], distortion or traction of neural roots [Smith, 1993;Nallamshetty et al, 2002], structural thinning and weakening of the sacrum leading to micro-fractures or instability, direct pressure on abdominal organs by anterior meningocele, shifts in cerebrospinal fluid volume, or increased pressure within focal cysts [Raftopoulos et al, 1993;Sonier et al, 1993;Ahn et al, 2000] (see Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies the symptoms reported most commonly include back pain (33/83; 40%), headache (11/36; 31%), leg pain (11/50; 22%), abdominal pain (4/40; 10%), motor deficits (4/43; 9%), sphincter disturbance (3/40; 8%) including incontinence or constipation, gait abnormalities, and neurological deficits (3/56; 5%) [Pyeritz et al, 1988;Raftopoulos et al, 1993;Smith, 1993;Sonier et al, 1993;Duncan and Esses, 1995;Sponseller et al, 1995;Ahn et al, 2000;Nallamshetty et al, 2002]. The most commonly reported symptoms in the current study-lower (or very low) back pain, headache, and leg painwere identical to the most common symptoms cited in prior studies (see Table VII).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 However, in most patients, the dural ectasia is asymptomatic. 60 Excessive accumulation or leakage of cerebrospinal fluid from the dural sac can cause postural hypotension and "low-pressure" headaches. 61,62 Damage of the dura from spinal taps or epidurals may not sufficiently heal, causing leakage, which also predisposes the patient to postural headaches.…”
Section: Dural Ectasiamentioning
confidence: 99%
“…It has been reported in 62% to 95% of patients with MFS [2,[12][13][14][15][16][17]. Diagnosis is made based on cross-sectional imaging of the spine.…”
Section: Marfan Syndromementioning
confidence: 99%